Answered

Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Factorise the following expression :​

Factorise The Following Expression class=

Sagot :

Answer:

The answer is "[tex](p-1) (pq-r^2)[/tex]"

Step-by-step explanation:

Given:

[tex]\to P ^2q-pr^2-pq+r^2\\\\[/tex]

Rearrange the above value:  

[tex]\to P ^2q-pr^2-pq+r^2 = p^2q-pq-pr^2+r^2\\\\[/tex]

                                    [tex]= pq(p-1)-r^2(p-1)\\\\= (p-1)(pq-r^2)\\\\[/tex]